Expert System Diagnosis Disease of Oil Palm Plants Using Forward Chaining and Dempster Shafer - Suriyati; Eny Maria; Annafi Franz (Politeknik Pertanian Negeri Samarinda, 2022)
This research is motivated by the problem of inhibiting crop production from oil palm plants, namely disease. Diseases of oil palm plants can be caused by viruses, fungi and, the host plant or an unfavorable environment. The process of diagnosing oil palm plant diseases requires expertise, knowledge and experience. Therefore, this study aims to build an expert system that can diagnose 9 types of plant diseases in oil palm from 29 symptoms based on the knowledge of 1 expert with the forward chaining method of reasoning and the web-based Dempster Shafer calculation method. The testing technique used is black box testing, validation testing, testing and theoretical calculations. The results of the black box test state that the expert system has 100% conformity in terms of functionality. The results of the expert validation test state that the expert system has 100% conformity. The results of the theoretical calculation test state that the expert system calculations are in accordance with the results of manual calculations. The results of the test with a questionnaire based on 32 respondents said it went very well. The results of this study provide the information needed by farmers to be able to diagnose and increase knowledge about how to overcome the problems faced by their oil palm plantations even without direct expert assistance in order to improve quality and stabilize the amount of production according to farmers' expectations.